Kinetic analysis of continuous reaction data for RAFT and free radical copolymerization with acrylic and styrenic monomers. (4th June 2021) - Siqueira, Julia S.; Florenzano, Fabio H.; Reed, Wayne F.
Abstract: Free radical (FR) and Reversible Addition Fragmentation Chain Transfer (RAFT) copolymerization rates for styrenic monomers in bulk and aqueous reactions were accelerated by acrylic comonomers, whose own rates were both delayed and decreased. The effect was found with styrenics as low as 0.6% by mole, and is directly observable from Automatic Continuous Online Monitoring of Polymerization reactions (ACOMP) data. Rapid radical transfer from acrylic to styrenic comonomer, through lower energy radical resonance stabilization in styrenics, was the suspected cause. FR and RAFT rates were equal, suggesting that FR termination controlled radical concentrations and rates. Despite strongly changing concentrations of initiator and comonomer radicals during reactions, the Quasi-Steady-State Approximation was demonstrated to hold. While rates were identical, molecular weights showed the characteristic increase with conversion for RAFT and decrease for FR. A new, generalized method for reactivity ratio determination was found and acceleration/deceleration behavior was consistently interpreted within a penultimate model. Graphical abstract: Image 1 Highlights: Real-time determination of comonomer gradients in living and RAFT copolymerization. New, generalized method of determining reactivity ratios. Kinetics of acceleration and inhibition in RAFT and free radical copolymerization. Experimental proof of the validity of the quasi-steady state approximation. Determining if penultimate instead of terminal model is needed in copolymerization.